Cross-reactivity of Schistosoma mansoni antigens and Timothy grass pollen allergens Phl p 1 and Phl p 5: blocking activity of rabbit Sm-SEA-induced IgG anti TGP antibodies - Ting, Tiew Ling (2017)
Western immunoblotting has been used to investigate IgG cross-reactivity between Schistosoma mansoni soluble egg antigens and crude extracts of the allergen Timothy grass pollen. Cross-reactivity was observed, with antibodies binding to allergen extracts also recognising epitopes present on the major immunogenic egg glycoproteins, namely IPSE/alpha-1, kappa-5 and omega-1. The blocking activity of cross-reactive rabbit IgG antibodies was tested using the RS-ATL8 basophil cell line, in which the cells were sensitised with human sera from patients allergic to Timothy grass pollen and activated with the pollen extract. Although minimal, some blocking ability of cross-reactive rabbit IgG antibodies was detected. The results are discussed in the context of hygiene hypothesis.